2007
DOI: 10.1016/j.brainres.2007.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant annexin 2 for fibrinolytic therapy in a rat embolic stroke model: A magnetic resonance imaging study

Abstract: Efficacy of recombinant annexin 2 (rAN II) in a rat model of embolic stroke was examined using a magnetic resonance imaging (MRI) and histology. The right middle cerebral artery of male Wistar rats was occluded by autologous clots under anesthesia. Four doses of rAN II (0.125, 0.25, 0.5 and 1.0 mg/kg, n = 10 for each group) or saline (1 ml/kg, n = 10) were administrated intravenously within 5 min before clot infusion. Serial changes in apparent diffusion coefficient (ADC) and relative blood flow (CBF) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…These include the findings that (1) local infusion of plasmin into the thrombus does not cause excessive bleeding within six-fold greater than the effective thrombolytic dose of tPA used (Marder et al, 2001); (2) antiplasmin quickly (in 1 sec) neutralizes plasmin that appears in the circulation (Marder et al, 2001), whereas tPA has longer half life (4 to 5 mins), and can cross the blood-brain barrier, whether damaged or intact, through low-density lipoprotein receptor-related protein-dependent and independent mechanisms, further weaking blood-brain barrier integrity and worsening brain damage (Benchenane et al, 2005;Yepes et al, 2003); (3) tPA can induce plasmin-independent MMP-9 up-regulation and microglia activation in stroke animal models (Aoki et al, 2002;Zhang et al, 2009). In addition, initial experimental evidence suggested that rA2 administration alone in vivo has not exhibited any organ specific or systematic complications (Ishii et al, 2001;Tanaka et al, 2007). These data, together with findings from this study, suggest, but do not prove, that optimization of the tPA-mediated fibrinolytic process may greatly improve the efficacy and safety of this form of stroke therapy.…”
Section: Discussioncontrasting
confidence: 54%
“…These include the findings that (1) local infusion of plasmin into the thrombus does not cause excessive bleeding within six-fold greater than the effective thrombolytic dose of tPA used (Marder et al, 2001); (2) antiplasmin quickly (in 1 sec) neutralizes plasmin that appears in the circulation (Marder et al, 2001), whereas tPA has longer half life (4 to 5 mins), and can cross the blood-brain barrier, whether damaged or intact, through low-density lipoprotein receptor-related protein-dependent and independent mechanisms, further weaking blood-brain barrier integrity and worsening brain damage (Benchenane et al, 2005;Yepes et al, 2003); (3) tPA can induce plasmin-independent MMP-9 up-regulation and microglia activation in stroke animal models (Aoki et al, 2002;Zhang et al, 2009). In addition, initial experimental evidence suggested that rA2 administration alone in vivo has not exhibited any organ specific or systematic complications (Ishii et al, 2001;Tanaka et al, 2007). These data, together with findings from this study, suggest, but do not prove, that optimization of the tPA-mediated fibrinolytic process may greatly improve the efficacy and safety of this form of stroke therapy.…”
Section: Discussioncontrasting
confidence: 54%
“…A better understanding of the regulation of the fibrinolytic system may lead to the identification of new therapeutic targets that might enhance endogenous fibrinolytic activity without inducing hemorrhagic sequelae. Recently, in a rat model of embolic stroke, infusion of recombinant A2 significantly reduced cerebral infarct size and increased cerebral blood flow without affecting systemic hemostatic parameters (11). A second recent report indicates that A2 infused in combination with t-PA in a rat model of embolic stroke reduces the effective dose of t-PA, thus preventing hemorrhage (12).…”
Section: A Either Anxa2mentioning
confidence: 99%
“…Third, injury-induced carotid artery thrombosis in rats can be averted by pretreatment with recombinant A2 (10). Fourth, cerebral infarct size can be reduced and cerebral blood flow can be increased, without affecting systemic hemostatic parameters, upon infusion of recombinant A2 alone or in combination with t-PA in a rat model of embolic stroke (11,12). Fifth, A2 is strikingly overexpressed in blast cells and is associated with hyperfibrinolytic hemorrhage in patients with acute promyelocytic leukemia (13).…”
mentioning
confidence: 99%
“…Stroke group (n = 6): Embolic stroke was induced following procedures reported previously (Tanaka et al, 2007). Briefly, the right carotid artery was exposed.…”
Section: Animal Preparationmentioning
confidence: 99%